Toward a Hermeneutic Theory of Social Practices - Ginev, Dimitri, author.
1 online resource
Keywords: "Recent methodological debates have shown that practice theory can either be developed by combining and slightly extending established theoretical concepts of inter-subjectivity, social normativity, collective behavior, interaction between agents and environment, habits, learning, collective intentionality, and human agency; or by following a strategy that promotes the quest for completely autonomous concepts. In the latter case, one defends a thesis of irreducibility.Towards a Hermeneutic Theory of Social Practices advocates this thesis by approaching the interrelational dynamic of social practices in terms of existential analytic. Indeed, this insightful volume outlines a methodology of the double hermeneutics that allows the study of the entanglement of agential plans, beliefs and intentions with configured practices; whilst also demonstrating how interrelated social practices with which agency is entangled articulate cultural forms of life.Suggesting a framework for studying the cultural forms of life within the scope of practice theory, this book will appeal to postgraduate students and postdoctoral researchers interested in fields such as Social Theory, Philosophy of Social Science and Research Methods for Social and Behavioural Sciences."--Provided by publisher.